2004
DOI: 10.1097/01.ju.0000138525.14552.1b
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Small Residual Stone Fragments Following Shock Wave Lithotripsy in Children

Abstract: Small RF after ESWL is clinically significant in children and increase the chance of adverse clinical outcome. These patients require close followup, particularly those with identifiable predisposing disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 17 publications
1
45
0
5
Order By: Relevance
“…A small study of 26 kidneys with residual fragments of ≤ 5 mm showed an adverse clinical outcome in 69% [22]. The presence of a metabolic abnormality was associated with stone growth.…”
Section: The Fate Of 'Clinically Insignificant Fragments' After Swlmentioning
confidence: 99%
“…A small study of 26 kidneys with residual fragments of ≤ 5 mm showed an adverse clinical outcome in 69% [22]. The presence of a metabolic abnormality was associated with stone growth.…”
Section: The Fate Of 'Clinically Insignificant Fragments' After Swlmentioning
confidence: 99%
“…Higher success rates have been achieved in the treatment of smaller stones.A renal pelvis stone smaller than 2 cm in diameter will be an ideal choice for ESWL treatment. [18][19][20][21][22][23] Dimensions, location, and composition of the stone, anatomy of the renal calyx, superposition of bone on ureter are the most important factors effecting success rates of ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…Afshar et al (45) evaluated the consequences of residual fragments following ESWL in the pediatric population. The data of 39 boys and 44 girls with a median age of 7 years and a mean follow up of 46 months who underwent ESWL were analysed.…”
Section: Retrograde Intrarenal Surgerymentioning
confidence: 99%